The reproductive pathologies of male offspring born to mothers with fetoplacental insufficiency: hormone dependent mechanisms of developing and profilaxis - Seliukova, N.; Misiura, K.; Kustova, S.; Boiko, M.; Korenieva, Ye.; Mykytyuk, M.; Karachentsev, Yu. (My University, 2022)
Introduction. Fetoplacental insufficiency (FPI) is the symptom complex that substantially results not only in pregnancy development and childbirth, but in the health condition of offspring at different times. It has been shown that offspring born to mothers with FPI have morphological and functional disturbances of different systems of organs. The aims of this research were to determine hormone depended mechanisms of reproductive pathologies developing in the ontogenesis of male offspring born to different aged mothers with FPI and experimental grounding of potential preventive activity of developed pharmaceutical composition suitable for animals of this phenotype. Materials and methods. Mature Wistar rat females of young (3–4 months) and mature (8-10 months) reproductive age have been used in the experiment. Eights groups for 7 pregnant females in each group have been formed. Modeling of FPI has been carried out by daily subcutaneous administration of the 50 % tetrachloromethane oil solution at dose of 2 ml/kg of body weight from 12th to 18th day of pregnancy. The reproductive system of male offspring has been estimated. Results. FPI influences the sex differentiation of brain in male offspring that reflects in delaying of sexual maturity in the form of postponed testicles moving to the scrotum. FPI leads to relative estrogenization, inhibition of sperm cells differentiation and causes significant changes in antioxidant defense system in male offspring at puberty. FPI causes changes of testosterone, estradiol levels and shifts sex hormones ratio to the hyperestrogenemia in the all of mature male offspring that influence the activity of male sexual behavior, worsens spermogram and fertility. Conclusion. Fetoplacental insufficiency in females in third trimester of pregnancy leads to marked changes in reproductive system of their male offspring born to mothers of reproductively young and reproductively mature age. Data obtained indicate the opportunity and ways to develop the medicines for prophylaxis of reproductive pathologies in children born to mothers with fetoplacental insufficiency
Keywords: fetoplacental insufficiency; pharmaceutical composition; reproductive disease; hormonal status; male offspring